The Effect of Life Style, Self Control and Financial Literacy on Financial Management with Consumptive Behavior as A Moderating Variable: Pengaruh Life Style, Self Control dan Financial Literacy Terhadap Pengelolaan Keuangan dengan Perilaku Konsumtif Sebagai Variabel Moderating - Lisdiana, Dela; Setiyono, Wisnu Panggah (Indonesian Journal of Innovation Studies, 2022)
This study aims to examine the effect of Life Style, Self Control and Financial Literacy on financial management with consumptive behavior as a moderating variable, a study of students at Muhammadiyah University of Sidoarjo. This research design is quantitative associative. The sample in this study used random sampling with a of 96 students from the University of Muhamadiyah Sidoarjo. The data used in this study is primary data taken by distributing questionnaires. The data analysis used in this study is SmartPLS with the aim of testing Life Style (X1), Self Control (X2), Financial Literacy (X3) on Financial Management (Y) with Consumptive Behavior (Z) as a moderating variable.The results of this study that Life Style, Self Control and Financial Literacy had a significant effect on financial management. While the Consumptive Behavior variable is able to moderate Self Control on Financial Management, the Consumptive Behavior variable is not able to moderate Life Style and Financial Literacy on Financial Management.